BOSTID applying science and technology to development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
BOSTID (Board on Science and Technology for International Development), a division of the US Office of International Affairs was established in 1969. It is responsible for programmes with developing countries. The Board examines ways of applying...